2007
DOI: 10.1002/art.22918
|View full text |Cite
|
Sign up to set email alerts
|

Do tumor necrosis factor inhibitors cause uveitis? A registry‐based study

Abstract: Objective. Population-based studies of patients with ankylosing spondylitis indicate that tumor necrosis factor (TNF) inhibitors prevent uveitis. Paradoxically, anecdotal reports implicate etanercept as a cause of uveitis. Therefore, using the information from 2 drug events databases, the purpose of this study was to assess reported cases of uveitis associated with the use of TNF inhibitors.Methods. Uveitis cases occurring in the US associated with etanercept, infliximab, or adalimumab therapy that were report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
160
0
26

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(188 citation statements)
references
References 32 publications
(42 reference statements)
2
160
0
26
Order By: Relevance
“…Several studies have reported flares or new-onset uveitis while on etanercept [65][66][67]. Evidence from national registries suggests that etanercept is associated with a greater number of uveitis cases than adalimumab or infliximab [68]. However, no definite causative effect of etanercept can be proved from these retrospective observational studies and the prescribing pattern of the different anti-TNFs may be a confounding factor [69].…”
Section: Biologic Drugsmentioning
confidence: 99%
“…Several studies have reported flares or new-onset uveitis while on etanercept [65][66][67]. Evidence from national registries suggests that etanercept is associated with a greater number of uveitis cases than adalimumab or infliximab [68]. However, no definite causative effect of etanercept can be proved from these retrospective observational studies and the prescribing pattern of the different anti-TNFs may be a confounding factor [69].…”
Section: Biologic Drugsmentioning
confidence: 99%
“…5 Lim et al have recently relied on a database of 2 drug events to assess reported cases of uveitis associated with the use of anti-TNFα. 5 They found that etanercept was associated with a significantly greater number of uveitis in comparison with infliximab and adalimumab.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Bu konuda yap›lan çal›flmalarda üveit harici çeflitli endikasyonlar nedeniyle etanersept kullanan hastalarda üveit s›kl›¤› artarken, infliksimab veya adalimumab kullan›lan gözlerde üveit s›kl›¤›n›n azald›¤› bildirilmifltir. [20][21] RA, psoriasis gibi pek çok hastal›kta etanersept ve infiliksimab benzer etkinlik gösterse de üveitte ve Crohn hastal›¤›nda etanersept flu an için tercih edilmemektedir. Genel kan› etanerseptinin Crohn hastal›¤›, Wegener granulomatozu ve sarkoidoz gibi granulamatöz hastal›k-larda baflar›s›z oldu¤u fleklindedir.…”
Section: Tnf Antagonistleriunclassified
“…Çünkü di¤er iki ajan›n bu sitokin üzerine bir etkisi bulunmamaktad›r. 20 Bu konudaki di¤er bir teori de, çözünebilir bir reseptör olan etanerseptin, göz için-de ba¤land›¤› TNF-α'n›n yar› ömrünü uzatarak üveit potansiyelini artt›rm›fl olabilece¤idir. 20 Bu etkinlik farkl›l›¤› ile ilgili ileri sürülen bir di¤er teori ise, etanerseptin Thücrelerinin sitokinlere olan yan›t›n› artt›r›rken, infliksimab›n azaltt›¤› fleklindedir.…”
Section: Tnf Antagonistleriunclassified
See 1 more Smart Citation